Pengaruh Pembelajaran Etnomatematika terhadap Hasil Belajar Matematika Siswa Kelas VI Sekolah Dasar - Mega Krisdiana; Heni Pujiastuti; Ila Rosmilawati (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research was motivated by the low mathematics learning outcomes of class VI students at UPT SDN Sentul 1 and the lack of use of learning media that linked it to local culture. The aim of this research is to determine the effect of ethnomathematics learning on the mathematics learning outcomes of sixth grade elementary school students. This study uses a quantitative approach. The research method used is quasi-experimental research. This research design uses a 2x2 factorial design. It can be concluded that the learning outcomes of sixth grade elementary school students in the material on integer arithmetic operations can be improved through ethnomathematics learning using linguistic media. This is proven by the results of the t test with Sig. 0.000 which means that Sig ≤ 0.05. Thus Ho is rejected, then µ1 ≠ µ2, that is, there is a difference in the mean scores using ethnomathematics learning and conventional learning. Other researchers should apply ethnomathematics-based mathematics learning and other innovative learning is needed, such as linking learning with traditional games, local cultural heritage and other local wisdom. So that students can not only improve their learning outcomes in mathematics subjects, but also gain new knowledge about local wisdom around them.